2019
DOI: 10.1111/jpi.12569
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes secondary hair follicle development of early postnatal cashmere goat and improves cashmere quantity and quality by enhancing antioxidant capacity and suppressing apoptosis

Abstract: Development of secondary hair follicles in early postnatal cashmere goats may be adversely affected by reactive oxygen species which cause oxidative stress. Because melatonin is a potent antioxidant and scavenger of free radicals, this study explored the effects of melatonin on secondary hair follicle development and subsequent cashmere production. It was found that the initiation of new secondary follicles in early postnatal Inner Mongolian cashmere goats of both melatonin‐treated and control goats occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 80 publications
(202 reference statements)
3
44
0
1
Order By: Relevance
“…In the current study, the population of primary hair follicles in the skin was the same for both melatonintreated and control cashmere goats and did not change over two consecutive cashmere growth cycles. This helps to con rm the view that the population of primary hair follicles in cashmere goats is established at birth and is not affected subsequently by treatment of adult cashmere goats with exogenous melatonin [8,[17][18][19]. In the case of secondary hair follicles, previous studies have also shown no effect of melatonin treatment on their total population, and thus no effect on S:P ratio [20,21].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In the current study, the population of primary hair follicles in the skin was the same for both melatonintreated and control cashmere goats and did not change over two consecutive cashmere growth cycles. This helps to con rm the view that the population of primary hair follicles in cashmere goats is established at birth and is not affected subsequently by treatment of adult cashmere goats with exogenous melatonin [8,[17][18][19]. In the case of secondary hair follicles, previous studies have also shown no effect of melatonin treatment on their total population, and thus no effect on S:P ratio [20,21].…”
Section: Discussionsupporting
confidence: 57%
“…Twenty-four female Inner Mongolian Cashmere goats were randomly allocated to two groups (n = 12): melatonin-treated (Melatonin) and control (Control) that were balanced for age, live weight and cashmere yield. Capsules containing melatonin were subcutaneously inserted behind an ear in cashmere goats on April 30 and June 30, 2016 at a dosage of 2 mg/kg live weight, which is based on our previous studies [3,8]. The melatonin implants were purchased from Kangtai Biotechnology Co., Ltd (Beijing, China) and can release melatonin sustainably for two months.…”
Section: Animals Experimental Design and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The hair of cashmere goats is divided into primary hair (guard hair) and secondary hair (ground hair or cashmere) [19,20]. The cashmere quality of cashmere goats has a signi cant relationship with the secondary hair follicles [21], but the speci c regulatory mechanism has not been fully explained. Therefore, the mechanism of action of DP cells on cashmere growth needs to be elucidated.…”
mentioning
confidence: 99%